John Wesley: Theologie in Predigten - Streiff, Patrick Philipp (Reutlinger Beiträge zur Theologie, 2019)
If you want to know more about John Wesley's theology, you have to read his sermons. Wesley did not write a dogmatic book, but tracts, appeals, journals and letters. But he shaped the Methodist renewal in the Church of England essentially through his preaching. The modern edition of his works collects 151 sermons, reaching from 1725 to 1791. The present study follows the development over the whole timespan. It shows where continuity lies and where the understanding of the Gospel evolves. It finds surprising new thoughts, particularly in the sermons of the elder Wesley. The study allows Wesley to speak on his own. Many quotes are published for the first time in German and thus give a chance to discover Wesley's theology through his preaching.